Dimensi Metrik Sisi Pada Beberapa Graf Unicyclic - Bayu Aprilianto; Dafik Dafik; Ermita Rizki Albirri (jcgant, 2020)
All the graphs in this paper are connected graphs and d(e,v) is the length of the shortest path between e=uv and v. Let G=(V,E) where V(G) is a set of vertex from graph G while E(G) is a set of edge from graph G. The edge metric dimension is a topic that is closely related to the cardinality of the distance of each edge on the graph G with respect to the resolving set W which is denoted by dim_E(G). Let if the subset of vertex W={w_1,w_2,w_3,..., w_k}, then the representation of the distance of the uv edge to the set of differences is k-tuple r(uv|W)=(d(uv,w_1),d(uv,w_2),d(uv,w_3),...,d(uv,w_k). A unicyclic graph is one that only has exactly one cycle. In this paper, we will study edge metric dimensions on some families of unicyclic graphs.